RISK FACTORS OF VULVOVAGINAL CANDIDIASIS IN DERMATO-VENEREOLOGY OUTPATIENTS CLINIC OF SOETOMO GENERAL HOSPITAL, SURABAYA, INDONESIA - Arfiputri, Dharin Serebrina; Hidayati, Afif Nurul; Handayani, Samsriyaningsih; Ervianti, Evy (African Journal of Infectious Diseases (AJID), 2018)
Background: Vulvovaginal Candidiasis (VVC) is one-third of vaginitis case. About 75% of women will have at least one episode of VVC. Complication of VVC can be unfavorable to impact the patient’s quality of life. Knowing its risk factors can prevent someone suffering from pathological VVC and its sequelae. The purpose of this study was to identify risk factors of VVC.Materials and Methods: A descriptive retrospective study was conducted by total sampling to 213 medical records of VVC patients from 869 fluor albus patients in Sexually Transmitted Infection (STI) Division, Dermatology and Venereology Outpatient Clinic in Dr. Soetomo General Hospital, Surabaya, East-Java, Indonesia in 2011 to 2013.Results: In 2011, 69 cases (22.77%) from 303 fluor albus patients, in 2012 69 cases (22.69%) from 304 fluor albus patients, and in 2013 75 cases (28.63%) from 262 fluor albus patients. As many as 180 (84.50%) of the patients were sexually active age group, which was 15-44 years old. Mostly patients were married (69.48%). As many as 167 (78.40%) sexual partners were patient’s husband. About 95 (44.13%) patients presented with recurrent VVC. Risk factors are previous STIs 74 (34.74%), vaginal douching (27.70%), pre-martial sexual intercourse (5.63%), other STIs (3.29%), diabetes mellitus (2.34%), gestation (1.88%), other fluor albus infections (0.94%), pantyliner (0.47%), and STIs in sexual partner (0,47%).Conclusion: Avoiding and/or managing risk factors is important to prevent VVC and its complications.